A composite catalyst for the selective oxidation of propylene to acrylic acid and a method for its preparation

CN121513892BActive Publication Date: 2026-10-30NINGBO JINYUANDONG PETROCHEM ENG TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511772582.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-28
Publication Date
2026-10-30
Estimated Expiration
2045-11-28

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种用于丙烯选择氧化制丙烯酸的复合催化剂及其制备方法,以解决现有丙烯一步法氧化制备丙烯酸的催化剂存在的选择性较差,催化剂机械强度差的问题

Benefits of technology

1、本发明提供的一种用于丙烯选择氧化制丙烯酸的复合催化剂的制备方法,将拟薄水铝石和氢氧化共同作为铝源,同时添加增强剂和造孔剂,同时通过分段煅烧的方法,使得制备的催化剂具有丰富的孔道和较高的比表面积,相比于现有技术通过共沉淀法制备的载体,提高了机械强度,且避免了现有沉淀法制备的载体存在的不同颗粒之间强度差异较大(方差和标准差大),影响催化剂的装填效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121513892B_ABST
    Figure CN121513892B_ABST
Patent Text Reader

Abstract

The application discloses a composite catalyst for preparing acrylic acid through selective oxidation of propylene and a preparation method thereof, and relates to the technical field of acrylic acid synthesis. The preparation method of the catalyst is as follows: (1) mixing pseudo-boehmite, aluminum hydroxide, a magnesium compound, a reinforcing agent and a pore-forming agent to form a mixture, adding nitric acid into the mixture to form a wet gel blank body with plasticity; drying, grinding and sieving the wet gel blank body, and then performing staged calcination and nitric acid treatment to obtain a magnesium-aluminum spinel carrier; (2) preparing metal salt solutions containing Mo, V, Cu, Ni, Ce and La, and preparing a complexing solution by adding ammonia water, loading the metals in the slurry onto the carrier by a ball milling method, and then performing surface boronization treatment, drying and calcination to obtain an active catalyst. The catalyst prepared by the application has good selectivity of acrylic acid in the preparation of acrylic acid through one-step oxidation of propylene, and has high mechanical strength and better stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of acrylic acid catalytic synthesis technology, specifically to a composite catalyst for the selective oxidation of propylene to acrylic acid and its preparation method. Background Technology

[0002] Acrylic acid is an important raw material and intermediate in modern chemical industry, and is a key ingredient in synthetic resins, plasticizers, leather, and other products. Its domestic and international demand is constantly increasing, which means a corresponding increase in the demand for catalysts. Currently, the industrial production of acrylic acid mainly adopts a two-step process: first, propylene is oxidized to acrolein, and then further oxidized to acrylic acid by introducing additional oxygen. The first stage uses a Mo-Bi catalyst to oxidize propylene to acrolein, and the second stage uses a Mo-V catalyst to further oxidize acrolein to acrylic acid. This process route can achieve high propylene conversion and acrylic acid yield, and has a mature process system and corresponding commercial catalyst products. However, it also has significant drawbacks: this process requires two different catalysts, two reactors, different operating conditions and control systems, and more monitoring points, resulting in large equipment investment and high energy consumption. Therefore, many engineers have chosen to shift their research focus to a one-step oxidation process for propylene to produce acrylic acid. This process not only has a simpler production route but also saves energy and equipment investment, offering significant economic benefits and practical significance.

[0003] The core technology for the one-step oxidation of propylene to acrylic acid is the development of a single catalyst capable of completing the process in a single reactor. For example, patent CN201310033400.8 describes a method for preparing a catalyst for the one-step catalytic oxidation of propylene to acrylic acid. This method uses molybdenum, vanadium, and niobium sources as raw materials, along with additives containing tellurium, antimony, phosphorus, potassium, and sodium. The relative molar ratios of molybdenum, vanadium, niobium, and additive elements A, X, and Y are 12:(1-12):(0-20):(1-10):(0-1):(0-1). A catalyst precursor is prepared using a co-precipitation method. The precursor is then calcined in an inert atmosphere at 300-750°C for 0.5-4 hours to obtain the catalyst for the one-step catalytic oxidation of propylene to acrylic acid. The propylene conversion rate is 75%-86%, the acrylic acid selectivity is 70%-85%, and the highest acrylic acid yield can reach 68.54%. Although this method improves the propylene conversion rate in a one-step reaction, the selectivity for acrylic acid is relatively poor.

[0004] Patent CN201310135699.8 discloses a catalyst and its preparation method for the one-step oxidation of propylene to acrylic acid. The method includes adding an organic complexing agent to a precursor compound solution of the catalyst components, heating and stirring until gelled, followed by drying and calcination to obtain the catalyst; or adding either silica sol or alumina sol to the catalyst precursor compound solution with the added organic complexing agent, adjusting the pH of the mixed solution to a range of 1-6 using a 6%-10% nitric acid solution or a 4%-10% ammonia solution, heating and stirring until gelled, followed by drying and calcination to obtain the catalyst. This method improves the selectivity of the catalyst, but it suffers from poor mechanical strength. Summary of the Invention

[0005] The purpose of this invention is to provide a composite catalyst for the selective oxidation of propylene to acrylic acid and its preparation method, so as to solve the problems of poor selectivity and poor mechanical strength of existing catalysts for the one-step oxidation of propylene to acrylic acid.

[0006] The objective of this invention is achieved through the following technical solution: A method for preparing a composite catalyst for the selective oxidation of propylene to acrylic acid specifically includes the following steps: (1) After thoroughly mixing boehmite, aluminum hydroxide, magnesium compound, reinforcing agent and pore-forming agent to form a mixture, nitric acid is added to the mixture, and the final mixture forms a plastic wet gel preform; The wet gel preform is dried, ground and sieved, then calcined in stages, and then the calcined material is treated with nitric acid to obtain a magnesium aluminum spinel carrier. (2) Prepare a salt solution by preparing a metal salt containing Mo, V, Cu, Ni, Ce and La, and add ammonia water to the salt solution to prepare a complexing solution; Magnesium aluminum spinel support is mixed with complexing liquid and then a control agent is added to form a slurry. The metal is loaded onto the support by ball milling to prepare a catalyst precursor. The catalyst precursor is then subjected to surface boronizing treatment, followed by washing, drying, and calcination to form an active catalyst.

[0007] Further, in step (1), the mass ratio of the pseudoboehmite and aluminum hydroxide, calculated as alumina, is 1:0.5-1.5; Add nitric acid to the mixture to control the pH of the mixture between 2.5 and 4.0.

[0008] In the carrier preparation process, a mixture of boehmite and aluminum hydroxide is selected as the aluminum source. The theoretical value of boehmite, calculated based on the mass of alumina, is 80%, but considering its purity and water absorption, the actual measured value should be recorded as 70%. The actual value of aluminum hydroxide, calculated based on the mass of alumina, is consistent with the theoretical value and can be recorded as 65%. The mass ratio of aluminum hydroxide to boehmite, calculated based on alumina, is between 1:0.5 and 1.5. Boehmite has high activity and helps to form abundant mesopores, while aluminum hydroxide decomposes more violently during calcination, which helps to generate larger channels or act as a template to guide the formation of macropores. Preferably, the mass ratio of aluminum hydroxide to boehmite, calculated based on alumina, is 1:1.05.

[0009] Further, in step (1), the magnesium compound is either magnesium hydroxide or magnesium oxide, and the total molar ratio of magnesium to aluminum is 1:2-3.5; preferably, the magnesium compound is magnesium hydroxide, and the total molar ratio of magnesium to aluminum is 1:2.

[0010] Further, in step (1), the reinforcing agent is calcium aluminate or calcium silicate, with calcium silicate being a further preferred choice; the mass of the reinforcing agent accounts for 10-25% of the total mass of the mixture, preferably, the mass of the reinforcing agent is 18% of the total mass of the mixture.

[0011] Further, in step (1), the pore-forming agent is sodium polyacrylate or guar gum powder, and the mass of the pore-forming agent is 0.2-12% of the total mass of the mixture; preferably, the pore-forming agent is sodium polyacrylate, and the mass of sodium polyacrylate is 6% of the total mass of the mixture.

[0012] Sodium polyacrylate is suitable for preparing high-strength, high-porosity, and uniformly distributed magnesium aluminum spinel materials. It can also achieve a balance between high porosity and low apparent porosity, making it suitable for applications requiring high mechanical strength and air permeability. It can also achieve precise control of pore structure and has good compatibility with inorganic systems.

[0013] Nitric acid is added to the mixture to ensure that the acid is in full contact with the powder (mixing and rolling). Under the combined action of the acid and sodium polyacrylate, the mixture forms a plastic wet gel preform, which is the basis for obtaining a uniform microstructure.

[0014] Further, in step (1), the wet gel blank is dried in a forced-air drying oven at 100-120°C for 1-2 hours to remove most of the moisture, and the dried material is ground and passed through a 100-mesh sieve.

[0015] Further, in step (1), the sieved powder is calcined in stages under an inert atmosphere (nitrogen atmosphere). The first stage calcination temperature is 300-500℃ and the calcination time is 1 hour to remove organic matter and water of crystallization. The second stage calcination temperature is 900-1100℃ and the calcination time is 2-4 hours. The heating rate during the stage calcination is controlled at 1-2℃ / min.

[0016] Segmented calcination can promote the formation of spinel crystal phase while preserving mesopores, thus preventing thermal stress from causing pore collapse.

[0017] Further, in step (1), the calcined precursor is post-treated: the calcined material is soaked in 0.1-1 mol / L nitric acid for 4 hours; after soaking, it is soaked and stirred in 50 times the volume of deionized water, repeated 3-5 times until the pH of the washing solution is close to neutral (pH=6-7), and then vacuum dried at 60-80℃ for 4-6 hours to prepare the magnesium aluminum spinel carrier.

[0018] Preferably, the concentration of the nitric acid solution is 0.5 mol / L.

[0019] Nitric acid can selectively dissolve amorphous phases or impurities on the surface, exposing mesopores and preventing moisture residue from causing pore collapse.

[0020] Furthermore, in step (2), the molar ratio of the metals Mo, V, Cu, Ni, Ce, and La in the metal salt containing Mo, V, Cu, Ni, Ce, and La is 12:3:1.5:0.5:0.3:0.2; Preferably, ammonia is added to the salt solution to control the pH of the salt solution to 10; Preferably, the total metal ion concentration in the complexing solution is 1.5 mol / L.

[0021] The ammonia added during the preparation of the complexing solution will undergo a coordination reaction with the metal ions to form stable ammonium-metal complex cations, such as [Ni(NH3)6]. 2+ wait.

[0022] Further, in step (2), the control agent is stearic acid, and the mass ratio of the complexing solution to the magnesium aluminum spinel carrier is 1:4; The mass of stearic acid is 2% of the total mass of the slurry.

[0023] Stearic acid, as an organic surfactant and process control agent, can effectively prevent powder agglomeration, thereby improving the overall fluidity of the slurry, making grinding more efficient and the powder particle size more uniform. In addition, the applied mechanical force can also cause partial decomposition of the ammonium complex or interaction with stearic acid. The carboxyl group of stearic acid combines with metal ions to form stearates, thereby achieving surface modification of the powder. Subsequently, the entire system is placed in a ball mill for reactive ball milling. Further, in step (2), the ball milling medium is selected as zirconia microspheres, the rotation speed is set to 400-600 rpm, and the ball milling time is 2-8 hours; preferably, the ball milling speed is set to 500 rpm and the ball milling time is 4 hours, so that the components can be dispersed at the nanoscale.

[0024] The wet slurry after ball milling is dried at 50-80℃ for 12-24 hours and then sieved to 80 mesh; preferably, the wet slurry is dried at 60℃ for 12 hours.

[0025] The functional composite powder obtained after sieving is mixed with a release agent, which is graphite, with an addition amount of 1-4%, preferably 2%.

[0026] After thorough mixing, the mixture is pressed into a cylindrical catalyst precursor with a diameter of 2-5 mm and a height of 2-5 mm. Preferably, it is pressed into a cylindrical catalyst precursor with a diameter of 5 mm and a height of 5 mm.

[0027] Further, in step (2), the surface of the formed catalyst precursor is boronized: the boron source solution is evenly distributed on the surface and pores of the catalyst precursor by the equal volume impregnation method, impregnated for 4 hours, and then cleaned with deionized water or organic solvent to remove residual boron source and by-products, and then dried. The surface-treated catalyst precursor is calcined at 400-450℃ for 2-8 hours.

[0028] Preferably, the boron source is sodium borohydride, boric acid, or boron oxide, and the calcination temperature is 400°C for 4 hours; Preferably, the boron source is sodium borohydride, and the concentration of sodium borohydride is 0.5-2 mol / L; more preferably, the concentration of sodium borohydride is 1 mol / L.

[0029] Boration treatment can weaken the overall acid strength, especially the excessively hard acid sites, optimize the distribution of acid centers, make it more suitable for structured catalysts, improve mass and heat transfer, and enhance overall performance.

[0030] The calcination process can remove process control agents and binders, and transform amorphous precursors into active catalysts with specific crystal phase structures.

[0031] The present invention also provides a composite catalyst for the selective oxidation of propylene to acrylic acid, specifically the composite catalyst is prepared by the above-described method for preparing composite catalysts.

[0032] The beneficial effects of this invention are as follows: 1. The present invention provides a method for preparing a composite catalyst for the selective oxidation of propylene to acrylic acid. The method uses boehmite and hydroxide as aluminum sources, and adds reinforcing agents and pore-forming agents. The catalyst is prepared by staged calcination, which results in abundant pores and a high specific surface area. Compared with the support prepared by the co-precipitation method in the prior art, the mechanical strength is improved, and the large strength difference (large variance and standard deviation) between different particles in the support prepared by the existing precipitation method is avoided, which affects the packing effect of the catalyst.

[0033] 2. The present invention provides a method for preparing a composite catalyst for the selective oxidation of propylene to acrylic acid. During the preparation of the support, the calcined material is acid-treated with nitric acid, which can selectively dissolve the amorphous phase or impurities on the surface of the support material, expose the mesopores, and avoid the collapse of the channels due to residual moisture. At the same time, it effectively removes the basic sites (such as free MgO) on the surface of the support, making the surface of the support tend to be weakly acidic or neutral, which is better adapted to the reaction of propylene oxidation to acrylic acid requiring appropriate acidic sites, and eliminating basic sites thereby improving the selectivity of acrylic acid.

[0034] 3. The present invention provides a method for preparing a composite catalyst for the selective oxidation of propylene to acrylic acid. By preparing a stable metal component complexing liquid and adding a control agent, the agglomeration of powder during ball milling can be effectively prevented, thereby improving the overall fluidity of the slurry, making ball milling more efficient, and the powder particle size more uniform. In addition, the applied mechanical force will also cause the partial decomposition of the ammonium complex in the complexing liquid or its interaction with stearic acid. The carboxyl group of stearic acid combines with metal ions to form stearate, thereby achieving surface modification of the powder and forming an organic layer on the catalyst surface, which can protect the active sites and inhibit side reactions such as sintering and deep oxidation.

[0035] 4. The present invention provides a method for preparing a composite catalyst for the selective oxidation of propylene to acrylic acid. By borizing the shaped catalyst precursor, the overall acid strength, especially the strong acid sites, is weakened, the distribution of acid centers is optimized, mass and heat transfer is improved, and the selectivity and stability of the catalyst are enhanced. Attached Figure Description

[0036] Figure 1 This is a schematic diagram of the finished catalyst prepared in Example 1 of the present invention. Detailed Implementation

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0039] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0040] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.

[0041] The reagents and equipment used in this invention are all known products or obtained by purchasing commercially available products.

[0042] The specific preparation method of the catalyst of the present invention is illustrated by the following examples.

[0043] Example 1 Preparation of magnesium aluminum spinel carrier Weigh 75g of boehmite, 77g of aluminum hydroxide, 65g of magnesium hydroxide, 51g of calcium silicate, and 17g of sodium polyacrylate. After thoroughly mixing the weighed components, add approximately 280ml of 1mol / L nitric acid dropwise, controlling the pH of the system to be below 4, to prepare a plastic wet gel preform.

[0044] The prepared wet gel preform was transferred to a forced-air drying oven and dried at 120°C for 2 hours to remove most of the moisture. The dried material was then ground and sieved (100 mesh).

[0045] The sieved powder was calcined in stages under a nitrogen atmosphere. The first stage calcination temperature was 300℃ and the calcination time was 1 hour. The second stage calcination temperature was 950℃ and the time was 3 hours. The heating rate during the first and second stage calcination processes was 2℃ per minute. After cooling to room temperature, the precursor was obtained.

[0046] The calcined precursor was post-treated by soaking it in 0.5 mol / L nitric acid for 4 hours. After soaking, it was soaked and stirred in 50 times the volume of deionized water and washed repeatedly until the pH of the washing solution was close to neutral (pH=6-7). After washing, it was vacuum dried at 80℃ for 4 hours to prepare the magnesium aluminum spinel carrier.

[0047] Loading of active components Weigh out 58.8g of ammonium molybdate, 8.8g of ammonium metavanadate, 9.1g of copper nitrate trihydrate, 3.6g of nickel nitrate hexahydrate, 3.3g of cerium nitrate hexahydrate, and 2.2g of lanthanum nitrate hexahydrate. Mix them and add 300mL of deionized water. Stir and dissolve at 50℃. Slowly add about 30mL of concentrated ammonia solution with a concentration of 15mol / L, and precisely control the pH at 10 to form a homogeneous and stable complex solution.

[0048] Mix 50 mL of the complexing solution with 200 g of magnesium aluminum spinel carrier powder, and add 2% stearic acid by weight. The total weight refers to the total weight of the complexing solution, magnesium aluminum spinel carrier powder, and stearic acid. Divide the mixture into four equal portions by weight and place them into four 500 mL ball mill jars. Add zirconium balls at a ball-to-material ratio of 10:1 (mass ratio of zirconium balls to material) and ball mill. Set the ball milling speed to 500 rpm and the ball milling time to 4 hours.

[0049] The wet paste was dried at 60°C for 24 hours and sieved to 80 mesh. The resulting functional composite powder was mixed with graphite release agent at an addition rate of 2%, which means that the amount of graphite added was 2% of the total mass of the functional composite powder and graphite. After thorough mixing, the mixture was pressed into cylinders with a diameter of 5 mm and a height of 5 mm to obtain the catalyst precursor.

[0050] The shaped catalyst precursor was impregnated in liquid phase and the surface was borated: a 1 mol / L NaBH4 solution was prepared, and the sodium borohydride solution was uniformly distributed on the surface and pores of the material by the equal volume impregnation method, and impregnation was carried out for 4 hours.

[0051] The surface-treated catalyst precursor was calcined at 400℃ for 4 hours to obtain the active catalyst. The finished product of the catalyst is shown in the figure.

[0052] Example 2 Preparation of magnesium aluminum spinel carrier Weigh 75g of boehmite, 77g of aluminum hydroxide, 43.5g of magnesium hydroxide, 46g of calcium silicate, and 15.4g of sodium polyacrylate. After thoroughly mixing the weighed components, add approximately 260ml of 1mol / L nitric acid dropwise, controlling the pH of the system to be below 4, to prepare a plastic wet gel preform.

[0053] The prepared wet gel preform was transferred to a forced-air drying oven and dried at 120°C for 2 hours to remove most of the moisture. The dried material was then ground and sieved (100 mesh).

[0054] The sieved powder was subjected to staged calcination under a nitrogen atmosphere. The first stage of calcination was carried out at 300℃ for 1 hour; the second stage of calcination was carried out at 950℃ for 3 hours. After cooling to room temperature, the precursor was obtained.

[0055] The calcined precursor was post-treated by soaking it in 0.5 mol / L nitric acid for 4 hours. After soaking, it was soaked and washed with 50 times its volume of deionized water, stirred, and repeated 5 times until the pH of the washing solution was close to neutral (pH=6-7). After washing, it was vacuum dried at 80℃ for 4 hours.

[0056] The same complexing solution was prepared according to the preparation method of the active metal complexing solution in Example 1, and the same preparation method was used to prepare the active catalyst.

[0057] Example 3 Preparation of magnesium aluminum spinel carrier Weigh 75g of boehmite, 77g of aluminum hydroxide, 52g of magnesium hydroxide, 48g of calcium silicate, and 16g of sodium polyacrylate. After thoroughly mixing the weighed components, add approximately 260ml of 1mol / L nitric acid dropwise, controlling the pH of the system to be below 4, to prepare a plastic wet gel preform.

[0058] The prepared wet gel preform was transferred to a forced-air drying oven and dried at 120°C for 2 hours to remove most of the moisture. The dried material was then ground and sieved (100 mesh).

[0059] The sieved powder was calcined in stages under a nitrogen atmosphere. The first stage of calcination was carried out at 300℃ for 1 hour; the second stage of calcination was carried out at 950℃ for 3 hours. After cooling to room temperature, the precursor was obtained.

[0060] The calcined precursor was post-treated by soaking it in 0.5 mol / L nitric acid for 4 hours. After soaking, it was soaked and stirred in 50 times the volume of deionized water and washed repeatedly until the pH of the washing solution was close to neutral (pH=6-7). After washing, it was vacuum dried at 80℃ for 4 hours to prepare the magnesium aluminum spinel carrier.

[0061] Loading of active components Weigh out 58.8g of ammonium molybdate, 8.8g of ammonium metavanadate, 9.1g of copper nitrate trihydrate, 3.6g of nickel nitrate hexahydrate, 3.3g of cerium nitrate hexahydrate, and 2.2g of lanthanum nitrate hexahydrate. Mix them and add 300mL of deionized water to dissolve them. After dissolving, slowly add about 30mL of concentrated ammonia solution with a concentration of 15mol / L, and precisely control the pH at 10 to form a homogeneous and stable complex solution.

[0062] Mix 50 mL of the complexing solution with 200 g of magnesium aluminum spinel carrier powder, and add 2% stearic acid by weight. The total weight refers to the total weight of the complexing solution, magnesium aluminum spinel carrier powder, and stearic acid. Divide the mixture into four equal portions by weight and place them into four 500 mL ball mill jars. Add zirconium balls at a ball-to-material ratio of 10:1 (mass ratio of zirconium balls to material) and ball mill. Set the ball milling speed to 500 rpm and the ball milling time to 4 hours.

[0063] The wet paste was dried at 60°C for 24 hours and sieved to 80 mesh. The resulting functional composite powder was mixed with graphite release agent at an addition rate of 2%, which means that the amount of graphite added was 2% of the total mass of the functional composite powder and graphite. After thorough mixing, the mixture was pressed into cylinders with a diameter of 5 mm and a height of 5 mm to obtain the catalyst precursor.

[0064] The shaped catalyst precursor was impregnated in liquid phase and the surface was borated: a 1 mol / L NaBH4 solution was prepared, and the sodium borohydride solution was uniformly distributed on the surface and pores of the material by the equal volume impregnation method, and impregnation was carried out for 4 hours.

[0065] The surface-treated catalyst precursor was calcined at 400℃ for 4 hours to obtain the active catalyst.

[0066] Comparative Example 1 Preparation of magnesium aluminum spinel carrier 703g of aluminum sulfate and 173g of magnesium sulfate were selected as the aluminum source and mixed with deionized water to prepare a 1mol / L metal salt solution. The solution was dissolved using ultrasound to form a homogeneous and stable salt solution. A 2mol / L sodium hydroxide aqueous solution was prepared as the alkali solution. The salt solution and alkali solution were added dropwise simultaneously to a base solution containing 100ml of deionized water. The coprecipitation reaction was controlled by a reactor with interlocked pH and flow controllers to maintain the pH of the reaction system between 9 and 11. The reaction temperature was maintained at 50-80℃ using a water bath, and the mixture was stirred at 500 rpm to ensure uniform mixing of the reactants and avoid excessively high local concentrations.

[0067] After the salt and alkali solutions were added dropwise simultaneously, the mixture was aged for 1 hour. The aged precipitate was then soaked and washed with deionized water by stirring, repeating this process multiple times until the pH of the washing solution was close to neutral (pH=6-7). After washing, the material was placed in a Buchner funnel for vacuum filtration until a filter cake was formed and no liquid dripped. The cake was then dried in a vacuum drying oven at 80°C for 4 hours and passed through a 100-mesh sieve to obtain magnesium aluminum spinel precursor powder. The powder was then heated to 900°C at a rate of 2°C / min and held at this temperature for 3 hours to prepare the magnesium aluminum spinel support.

[0068] The same complexing solution was prepared according to the preparation method of the active metal complexing solution in Example 1, and the same preparation method was used to prepare the active catalyst.

[0069] Comparative Example 2 Preparation of magnesium aluminum spinel carrier Weigh 75g of boehmite, 77g of aluminum hydroxide, 65g of magnesium hydroxide, 51g of calcium silicate, and 17g of sodium polyacrylate. After thoroughly mixing the weighed components, add approximately 280ml of 1mol / L nitric acid dropwise, controlling the pH of the system to be below 4, to prepare a plastic wet gel preform.

[0070] The prepared wet gel preform was transferred to a forced-air drying oven and dried at 120°C for 2 hours to remove most of the moisture. The dried material was then ground and sieved (100 mesh).

[0071] The sieved powder was subjected to staged calcination under a nitrogen atmosphere. The first stage of calcination was carried out at 300℃ for 1 hour; the second stage of calcination was carried out at 950℃ for 3 hours. After cooling to room temperature, the precursor was obtained.

[0072] The calcined precursor was post-treated by soaking it in 0.5 mol / L nitric acid for 4 hours. After soaking, it was soaked and stirred in 50 times the volume of deionized water and washed repeatedly until the pH of the washing solution was close to neutral (pH=6-7). After washing, it was vacuum dried at 80℃ for 4 hours to prepare the magnesium aluminum spinel carrier.

[0073] Loading of active components Weigh out 58.8g of ammonium molybdate, 8.8g of ammonium metavanadate, 9.1g of copper nitrate trihydrate, 3.6g of nickel nitrate hexahydrate, 3.3g of cerium nitrate hexahydrate, and 2.2g of lanthanum nitrate hexahydrate. Mix them and add 300mL of deionized water. Stir and dissolve at 50℃. Slowly add about 30mL of concentrated ammonia solution with a concentration of 15mol / L, and precisely control the pH at 10 to form a homogeneous and stable complex solution.

[0074] Mix 50 mL of the complexing solution with 200 g of carrier powder, add 2% stearic acid by weight, divide into 4 equal portions by weight, place in 4 ball mill jars (500 mL ball mill jars), add zirconium balls, the ball-to-material ratio is 10:1 (mass ratio of zirconium balls to material), set the ball milling speed to 500 rpm, and the ball milling time is 4 hours.

[0075] The wet paste was dried at 60°C for 24 hours and sieved to 80 mesh. The resulting functional composite powder was mixed with graphite release agent at a dosage of 2%. After thorough mixing, the mixture was pressed into cylinders with a diameter of 5 mm and a height of 5 mm to obtain the catalyst precursor.

[0076] The catalyst precursor without surface treatment was directly calcined at 400℃ for 4 hours to prepare the active catalyst.

[0077] Comparative Example 3 Preparation of magnesium aluminum spinel carrier Weigh 75g of boehmite, 77g of aluminum hydroxide, 52g of magnesium hydroxide, 48g of calcium silicate, and 16g of sodium polyacrylate. After thoroughly mixing the weighed components, add approximately 260ml of 1mol / L nitric acid dropwise, controlling the pH of the system to be below 4, to prepare a plastic wet gel preform.

[0078] The prepared wet gel preform was transferred to a forced-air drying oven and dried at 120°C for 2 hours to remove most of the moisture. The dried material was then ground and sieved (100 mesh).

[0079] The sieved powder was calcined in a nitrogen atmosphere at a heating rate of 2℃ / min, a calcination temperature of 950℃, and a holding time of 3 hours. After cooling to room temperature, the powder was removed to obtain magnesium aluminum spinel carrier particles.

[0080] Loading of active components Weigh out 58.8g of ammonium molybdate, 8.8g of ammonium metavanadate, 9.1g of copper nitrate trihydrate, 3.6g of nickel nitrate hexahydrate, 3.3g of cerium nitrate hexahydrate, and 2.2g of lanthanum nitrate hexahydrate. Mix them and add 300mL of deionized water to dissolve them. After dissolving, slowly add about 30mL of concentrated ammonia solution with a concentration of 15mol / L, and precisely control the pH at 10 to form a homogeneous and stable complex solution.

[0081] Mix 50 mL of the complexing solution with 200 g of magnesium aluminum spinel carrier powder, and add 2% stearic acid by weight. The total weight refers to the total weight of the complexing solution, magnesium aluminum spinel carrier powder, and stearic acid. Divide the mixture into four equal portions by weight and place them into four 500 mL ball mill jars. Add zirconium balls at a ball-to-material ratio of 10:1 (mass ratio of zirconium balls to material) and ball mill. Set the ball milling speed to 500 rpm and the ball milling time to 4 hours.

[0082] The wet paste was dried at 60°C for 24 hours and sieved to 80 mesh. The resulting functional composite powder was mixed with graphite release agent at an addition rate of 2%, which means that the amount of graphite added was 2% of the total mass of the functional composite powder and graphite. After thorough mixing, the mixture was pressed into cylinders with a diameter of 5 mm and a height of 5 mm to obtain the catalyst precursor.

[0083] The shaped catalyst precursor was impregnated in liquid phase and the surface was borated: a 1 mol / L NaBH4 solution was prepared, and the sodium borohydride solution was uniformly distributed on the surface and pores of the material by the equal volume impregnation method, and impregnation was carried out for 4 hours.

[0084] The surface-treated catalyst precursor was calcined at 400℃ for 4 hours to obtain the active catalyst.

[0085] The catalysts prepared in Examples 1 and 3, as well as Comparative Examples 1-2, were characterized by BET, and the specific results are shown in Table 1 below.

[0086] Table 1

[0087] As can be seen from the BET characterization data in Table 1, the catalyst prepared in Example 1 has a significantly higher specific surface area compared to that prepared in Comparative Example 1. This indicates that when the support prepared by the method of the present invention is used to prepare an active catalyst, compared to the support prepared by the conventional method in Comparative Example 1, the catalyst prepared by the method of the present invention is more beneficial for improving catalyst activity. In Table 1, although the magnesium aluminum spinel support prepared by the conventional method in Comparative Example 1 has a higher total pore volume than that in Examples 1 and 3, its pore size distribution shows that the catalyst in Comparative Example 1 is basically mesoporous, meaning the pore size is small, which is not conducive to substrate entry into the pores, thus reducing the number of active sites and affecting the catalyst activity. The catalyst prepared in Comparative Example 2 has not undergone borylation treatment. Although the pore size is improved compared to Comparative Example 1, the final catalyst exhibits a poorer specific surface area and total pore volume.

[0088] To further evaluate the catalyst's performance, specific test conditions for catalyst activity and selectivity were established: performance was evaluated in a fixed-bed reactor (25 mm inner diameter), bed height 5 cm, catalyst loading 30 g, reaction temperature 290-320 °C, pressure 0.1 MPa, feed gas ratio of propylene:air:water vapor = 1:8:1.5, and overall feed gas space velocity 1300 h⁻¹. -1 The specific test results are shown in Table 2.

[0089] Table 2

[0090] In Table 2 above, the bed temperature is the actual temperature detected by the thermocouple, the set temperature is the set temperature for fixed bed heating, and the reaction is an exothermic reaction. Therefore, the actual temperature will be higher than the set temperature.

[0091] As can be seen from the data in Table 2 above, the catalyst prepared by the conventional method has a lower propylene conversion rate and lower acrylic acid selectivity compared with Example 1. Although the catalyst prepared by Comparative Example 2 without boronizing treatment has no significant impact on activity, it does affect the selectivity of acrylic acid.

[0092] In the carrier preparation process, only one calcination was performed, and no post-treatment was carried out on the calcined precursor. As shown in Comparative Example 3, the change in acrylic acid conversion rate was not significant, but the selectivity of acrylic acid was still reduced. This is mainly because the spinel prepared by direct calcination (i.e., single calcination) may have uneven crystallinity and irregular pore structure, easily forming magnesium oxide and aluminum oxide impurities, resulting in incomplete spinel phase formation. Segmented calcination, on the other hand, allows for sufficient atomic diffusion, forming a high-purity spinel structure, avoiding impurities, and better controlling the evolution of the pore structure. This provides more anchoring sites for active components (such as molybdenum, vanadium, bismuth, etc.), making them highly dispersed, which is beneficial for the mass transfer and diffusion of reactants (propylene) and products (acrylic acid), reducing side reactions, and thus improving the catalyst's selectivity for acrylic acid. Nitric acid treatment can effectively remove basic sites (such as free MgO) from the surface, making the surface more weakly acidic or neutral. The oxidation of propylene to acrylic acid requires moderate acidic sites; basic sites promote side reactions, leading to over-oxidation of acrylic acid to carbon dioxide. Eliminating basic sites through nitric acid treatment can improve the selectivity of acrylic acid.

[0093] In the reaction process of propylene oxidation to prepare acrylic acid, a catalyst with high mechanical strength can avoid easy wear during the reaction, thus affecting the catalyst's service life. Therefore, the mechanical strength of the catalyst was specifically tested. The mechanical strength of the catalyst was determined by measuring the crushing strength of a single catalyst particle using a particle strength tester (particles that are not broken are not included). Here, the lateral compressive strength of the catalyst was measured, which refers to the strength required to radially crush the catalyst particles. The specific sampling test results of the catalyst mechanical strength are shown in Table 3 below.

[0094] Table 3

[0095] As can be seen from the test results of the mechanical strength of the prepared catalysts in Table 3 above, the catalyst prepared by the conventional method in Comparative Example 1 after loading the active component has poor pressure resistance. The catalyst in Comparative Example 2, which was not borated, has better average pressure resistance, but there are large differences between the catalysts, and the pressure resistance varies.

[0096] Therefore, the catalysts prepared in Comparative Example 1 and Comparative Example 2 have significant differences in pressure resistance. When loaded into the reactor, they are prone to uneven bed compaction, resulting in voids or "bridging," which leads to uneven fluid distribution in the reactor and causes flow deviation or channeling. Alternatively, they may break and generate powder during loading or operation, clogging the bed pores, increasing the pressure drop, and causing local overheating ("hot spots") or runaway temperatures. Ultimately, this leads to a decrease in catalyst selectivity, a reduction in product yield, and an impact on catalyst lifespan.

[0097] The above description is merely a preferred embodiment of the present invention, and should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a composite catalyst for the selective oxidation of propylene to acrylic acid, characterized in that, Specifically, the steps include the following: (1) After thoroughly mixing boehmite, aluminum hydroxide, magnesium compound, reinforcing agent and pore-forming agent to form a mixture, add nitric acid to the mixture until a plastic wet gel preform is formed; The wet gel preform is dried, ground and sieved, then calcined in stages, and then the calcined material is treated with nitric acid to obtain a magnesium aluminum spinel carrier. (2) Prepare a salt solution by preparing a metal salt containing Mo, V, Cu, Ni, Ce and La, and add ammonia water to the salt solution to prepare a complexing solution; Magnesium aluminum spinel support is mixed with complexing liquid and then a control agent is added to prepare a slurry. The metal in the slurry is loaded onto the support by ball milling to prepare a catalyst precursor. The catalyst precursor is then subjected to surface borylation treatment, washing, drying and calcination to form an active catalyst. The reinforcing agent mentioned in step (1) is calcium aluminate or calcium silicate; In step (1), the sieved powder is calcined in stages under an inert atmosphere. Specifically, the first stage calcination temperature is 300-500℃ and the calcination time is 1 hour to remove organic matter and water of crystallization. The second stage calcination temperature is 900-1100℃ and the calcination time is 2-4 hours. The heating rate during the stage calcination is controlled at 1-2℃ / min. The control agent in step (2) is stearic acid.

2. The method for preparing the composite catalyst according to claim 1, characterized in that, In step (1), the mass ratio of aluminum hydroxide to boehmite, calculated as alumina, is 1:0.5-1.5; The magnesium compound mentioned in step (1) is either magnesium hydroxide or magnesium oxide, and the total molar ratio of magnesium to aluminum is 1:2-3.

5.

3. The method for preparing the composite catalyst according to claim 1, characterized in that, The reinforcing agent accounts for 10-25% of the total mass of the mixture; The pore-forming agent mentioned in step (1) is sodium polyacrylate or guar gum powder, and the mass of the pore-forming agent is 0.2-12% of the total mass of the mixture.

4. The method for preparing the composite catalyst according to claim 1, characterized in that, The calcined precursor undergoes post-treatment, specifically as follows: The calcined material was soaked in 0.1-1 mol / L nitric acid for 4 hours. After soaking, it was soaked and stirred in 50 times the volume of deionized water, and the process was repeated 3-5 times until the pH of the washing solution was 6-7. Then, it was vacuum dried at 60-80℃ for 4-6 hours to prepare the magnesium aluminum spinel carrier.

5. The method for preparing the composite catalyst according to claim 1, characterized in that, In step (2), the molar ratio of the metals Mo, V, Cu, Ni, Ce and La in the metal salt containing Mo, V, Cu, Ni, Ce and La is 12:3:1.5:0.5:0.3:0.

2.

6. The method for preparing the composite catalyst according to claim 1, characterized in that, The mass ratio of the complexing solution to the magnesium aluminum spinel carrier is 1:4; The mass of stearic acid is 2% of the total mass of the slurry.

7. The method for preparing the composite catalyst according to claim 1, characterized in that, In step (2), the milling media is selected as zirconia balls, the rotation speed is set to 400-600 rpm, and the milling time is 2-8 hours; The wet slurry after ball milling is dried at 50-80℃ for 12-24 hours, and then passed through an 80-mesh sieve. The functional composite powder obtained after sieving is mixed with the release agent graphite. The amount of graphite added is 1-4% of the total mass of the functional composite powder and graphite. After thorough mixing, it is pressed into a cylindrical catalyst precursor with a diameter of 2-5 mm and a height of 2-5 mm.

8. The method for preparing the composite catalyst according to claim 7, characterized in that, The surface of the pressed catalyst precursor is subjected to boronizing treatment. The specific boronizing treatment method is as follows: the boron source solution is evenly distributed on the surface and pores of the catalyst precursor by the equal volume impregnation method, and impregnation is carried out for 4 hours. After boronizing treatment, it is washed with deionized water or organic solvent to remove residual boron source and by-products, and then dried. The surface-treated catalyst precursor is calcined at 400-450℃ for 2-8 hours. The boron source is sodium borohydride, boric acid, or boron oxide, and the concentration of the boron source solution is 0.5-2 mol / L.

9. A composite catalyst for the selective oxidation of propylene to acrylic acid, characterized in that, The composite catalyst is prepared by the method according to any one of claims 1-8.

Citation Information

Patent Citations

  • A method for preparing a catalyst for the one-step catalytic oxidation of propylene to acrylic acid.

    CN103071514B

  • Catalyst used in preparation of acrylic acid through one-step oxidation of propylene and preparation method thereof

    CN103285888A

  • Preparation method of sulfur-resistant carbon monoxide shift catalyst carrier

    CN103182311A

  • Catalyst with mo, v, NB and process for preparing unsaturated acids

    GB1566314A